Musical resonances in the body and on the scene of black performance - Flávia Cristina Honorato dos Santos; Renata de Lima Silva (Kabilaewatala) (Revista Brasileira de Estudos da Presença)
Considering the power of musicality in the performing arts as a device for body states and, also, with regard to the textures and ambiences that collaborate with dramaturgy, this article addresses the relationship between body, scene, music and Afro-Brazilian culture. To this end, the experience with the show Por cima do mar eu vim, produced by Núcleo Coletivo 22, in the city of Goiânia (GO), is used to discuss the way in which Afro-Amerindian musicality is capable of giving outlines to the contemporary scene, in order to attribute to it identity traits of what we can call black performance and Afro-Amerindian poetics, for instance.